2020
DOI: 10.3390/ijerph17176230
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Social Dimensions into Future Sustainable Energy Supply Networks

Abstract: Environmental protection and sustainable development have become an inevitable trend in many areas, including the energy industry. The development of energy supply networks is strongly correlated with the economics of energy sources as well as ecological and socio-political issues. However, the energy supply network is often distant from the social perspective. This paper therefore combines examination of perceptions and awareness of general public (web-based questionnaire) and top energy experts (a Delphi sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…This will also be consistent with a combination of United Nation (UN) Sustainable Development Goals: “Responsible consumption and production”; “Affordable and clean energy”; “Sustainable cities and communities” as well as “Industry innovation and infrastructure”. Energy system would also become leaner, more efficient, digitalized and smarter, and their general performance would increase which is in accordance with findings of Obrecht et al (2020).…”
Section: Discussionsupporting
confidence: 83%
“…This will also be consistent with a combination of United Nation (UN) Sustainable Development Goals: “Responsible consumption and production”; “Affordable and clean energy”; “Sustainable cities and communities” as well as “Industry innovation and infrastructure”. Energy system would also become leaner, more efficient, digitalized and smarter, and their general performance would increase which is in accordance with findings of Obrecht et al (2020).…”
Section: Discussionsupporting
confidence: 83%
“…The least represented was the social dimension (68.10%). The social dimension is understudied and will follow the environmental dimension in priority in the next five years [152]. It is already increasing in importance among socially responsible companies that assess and monitor social responsibility not just for themselves but also for their Tier-1, Tier-2, Tier-n sub-suppliers, recently being practiced in food supply chains and some clothing manufacturers.…”
Section: Discussionmentioning
confidence: 99%
“…However, as many studies was shown, that it can also be used to check the achievement of sustainable development goals [35] or prioritizing sustainable urban regeneration in sensitive areas [36], which points to its universality. Based on the literature data [8,9,15,37,38,39,40,41,42,43], the main factors for individual groups of the analysis were determined, i.e. strengths, weaknesses, opportunities, threats.…”
Section: Methodology Of Researchmentioning
confidence: 99%